APLIKASI SISTEM GPS KEGIATAN OPERASIONAL PERSAMPAHAN DINAS PENGELOLAAN SAMPAH, PERTAMANAN DAN PEMAKAMAN (DP4) KOTA SUKABUMI: Yasmi Afrizal, Julian Chandra W - Jurnal, Redaksi Tim (PETIR, 2019)
The increasing the number of population and the diversity activities in sukabumi caused the general problems on infrastructure service such as waste transportation. During the process of data collection and monitoring of waste operational vehicles at the Department of Waste Management, Parks and Cemeteries (DP4) of Sukabumi can not be done optimally because of the existing information systems limitations. So the presence of the vehicle where it in the field cannot be observed directly. The lack of strict supervision in the use of this operational vehicles facility caused the misuse of vehicles in the works. This Research aimed to find the problems solutions by made an application for monitoring waste operational vehicles by utilizing GPS and GIS technology, so that the concerned parties especially DP4 of Sukabumi can monitor the movement of freight and make an appropriate decision if there are some problems that happen during the trip. The applications have been made to speed up the searching process of the vehicle operational position and to find out who operate these vehicles without directly supervision to the field, so that the misuse of vehicle operation can be reduced.